Lingkungan Hidup Di Desa Pakraman Penglipuran: Kajian Teologi Hindu - I Gede Januariawan (Jayapangus Press, 2019)
The village community still holds to the tradition in the midst of the current globalization. People still hold on to local wisdom inherited from generation to generation. This is also done by the community in preserving the environment. The people of Penglipuran Pakraman Village adheres to Hinduism so that Hindu theology influence is certainly very strong. Based on this background, it is investigated more deeply about the environmental concepts based on Hindu theology, the implementation of environmental management system based on Hindu Theology, and the environmental sustainability implications in Penglipuran Pakraman village in socio cultural and religious. To discuss the problem is used several theories they are: Hermeneutics Theory, Symbol Theory, Functionalism Structural Theory. The results of the research are: There are local Theological concepts in Pakraman Penglipuran village which are deeply in harmony with Hindu Theology establishing the confidence of the people to guard the preservation of the environment such as the worship of Ratu Sakti Empu Naluah. This is in accordance with the Vedic teachings that strongly prohibit forest destruction. Pakraman Penglipuran village include: Environmental management system in PenglipuranPakraman Village is really simple but all the system works properly. The rules are clear and the enforcement is also firm so that the community is very obedient to the customary law. The implementation of the Hindu Theology concept is also manifested in religious rituals. The implications of environmental sustainability for the rural life of Pakraman PenglipuranVillage include the socio-cultural and religious implications. Socially Pakraman Penglipuran Village as a tourist destination brings implications to the economy of the community. The income of the population increases because they no longer rely solely on livelihoods in the agricultural sector. The findings of this study (1) the strategy of the Penglipuran community to take a middle way between maintaining traditional values in managing the environment and adapting to the progress of modern era by deviding the living space into two, the front maintaining traditional values while the back part follows the modern era (2) The strength of the community maintains traditional values in managing the environment because of the theological that had been internalized in each individual in the community, (3) Penglipuran became village model that perfomed well environmental management.